Enhancing the MSMEs' Performance Through Strategic Flexibility: Does Competitive Intensity Matter? - Hidayatullah, Nur Adinda; Darmawan, Baziedy Aditya (MEC-J (Management and Economics Journal), 2025)
Despite being a key driver of the national economy, Micro, Small, and Medium Enterprises (MSMEs) continue to face significant challenges in enhancing their performance. While prior research has examined various factors influencing MSMEs' performance, limited attention has been given to the role of strategic flexibility and competitive intensity. This study aims to investigate the impact of strategic flexibility on MSMEs' performance, with competitive intensity as a moderating factor. To achieve this, the study involved 80 MSMEs from Yogyakarta and Sleman in data collection. Subsequently, the data was examined by employing a Partial Least Squares Structural Equation Modeling (PLS-SEM), ensuring a comprehensive evaluation of the proposed relationships. The findings reveal that strategic flexibility plays a direct role in improving MSMEs' performance, regardless the level of competitive intensity. This insight offers valuable theoretical contributions while also providing practical managerial implications for MSME owners and managers, emphasizing the importance of cultivating strategic flexibility to sustain business growth in an increasingly dynamic market environment.